1996
DOI: 10.1016/0014-5793(96)00734-x
|View full text |Cite
|
Sign up to set email alerts
|

NMR structures of a mitochondrial transit peptide from the green alga Chlamydomonas reinhardtii

Abstract: The 26-amino-acid pre-sequence of the ATP synthase subunit that directs the protein from the cytosol to mitochondria in the unicellular green alga Chlamydomonas reinhardtii has been synthesised and analysed using NMR spectroscopy/circular dichroism and compared to a chloroplast transit peptide from the same organism. The results demonstrate that the peptide, though mainly unstructured in water, undergoes a strong conformational change in a 36% water/64% 2,2,2-trifluoroethanol mixture. In this solvent condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 30 publications
0
21
0
Order By: Relevance
“…The internal segment between the N‐ and C‐terminal domains is enriched in proline indicating that it is a more flexible part of the presequence. The C‐terminal part of the pF 1 β presequence has been previously shown to interact with both the spinach MPP/ bc 1 complex and rat MPP (Sjöling et al ., 1994; Sjöling et al ., 1996). Therefore, this study focused on the C‐terminal part of the presequence.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The internal segment between the N‐ and C‐terminal domains is enriched in proline indicating that it is a more flexible part of the presequence. The C‐terminal part of the pF 1 β presequence has been previously shown to interact with both the spinach MPP/ bc 1 complex and rat MPP (Sjöling et al ., 1994; Sjöling et al ., 1996). Therefore, this study focused on the C‐terminal part of the presequence.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, a proline residue between the distal and proximal arginines (Hammen et al ., 1996; Niidome et al ., 1994; Ogishima et al ., 1995; Thornton et al ., 1993) and individual residues at positions +1, +2 and +3 from the cleavage site were shown to be of importance (Klaus et al ., 1996; Lain et al ., 1998; Ogishima et al ., 1995). It has also been suggested that MPP recognizes higher‐order structural elements (Hammen et al ., 1994; Luciano and Géli, 1996; Sjöling and Glaser, 1998; Sjöling et al ., 1994; Sjöling et al ., 1996; Waltner and Weiner, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…The content of Pro and Ser residues is higher in cTPs, while the prevalence of basic amino acid residues is higher in mTPs. mTPs have been shown to form amphiphilic α‐helices in membrane mimetic media , and it has been demonstrated that they bind with their hydrophobic side into a hydrophobic groove in the Tom20 receptor . An N‐terminal α‐helix has been observed in the targeting peptides both in alternative oxidase (AOX) and in F 1 β in SDS micelles, which also appears to be important for targeting.…”
Section: Discussionmentioning
confidence: 99%
“…The mTPs are on average 42 amino acid residues long and contain more arginines especially in the N‐terminal portion of the mTPs, while the cTPs are on average 58 amino acid residues long and contain more serines and prolines . Structurally, most mTPs are predicted to form an amphiphilic α‐helix, which has been shown to play an important role in mitochondrial import , while cTPs appear to be unstructured in most studies . Nevertheless, some cTPs have been reported to form helical structures in a membrane mimetic environment .…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Another important aspect for mitochondrial proteins is the propensity for their presequences to form an amphiphilic α-helix. 13,14 The hydrophobic side of the amphiphilic α-helix has been shown to bind to a hydrophobic groove in the import receptor Tom20. 15,16 The amphiphilic α-helix of a plant presequence have also been shown to bind to the plant import receptor Tom20.…”
Section: Introductionmentioning
confidence: 99%